2002
DOI: 10.1897/1551-5028(2002)021<2581:tcopaa>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

The Concept of Persistence as Applied to Metals for Aquatic Hazard Identification

Abstract: The criteria persistence (P), bioaccumulation (B), and toxicity (T) are applied by domestic and international regulators and modelers to the hazard identification of chemical substances, including metals and metalloids, that may present harm to the environment. In this paper, we critically examine the literature to determine the weight of evidence for the application of water column partition half-times as a surrogate for the persistence criterion in the aquatic hazard identification of metals and metal compou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Thus, Di define persistence as "a characteristic of a metal that is indicative of the constancy and duration of exposure of the available metal forms in a particular medium" -the emphasis is on the bioavailable metal form, not the total metal. Similarly, Skeaff et al (2002) suggest that persistence can only reasonably be determined based on the partition half-life of the bioavailable fraction of the total dissolved metal concentration determined in the laboratory under standardized conditions. SAB (2002) recommends stability and environmental residence time as more appropriate than persistence "for characterizing the temporal dynamics of metals" and also notes that, for metals, persistence may be protective rather than detrimental.…”
Section: Hazard Identificationmentioning
confidence: 99%
“…Thus, Di define persistence as "a characteristic of a metal that is indicative of the constancy and duration of exposure of the available metal forms in a particular medium" -the emphasis is on the bioavailable metal form, not the total metal. Similarly, Skeaff et al (2002) suggest that persistence can only reasonably be determined based on the partition half-life of the bioavailable fraction of the total dissolved metal concentration determined in the laboratory under standardized conditions. SAB (2002) recommends stability and environmental residence time as more appropriate than persistence "for characterizing the temporal dynamics of metals" and also notes that, for metals, persistence may be protective rather than detrimental.…”
Section: Hazard Identificationmentioning
confidence: 99%
“…Heavy metals are ubiquitous materials within the environment, which can originate from both natural as well as anthropogenic sources (Markert and Friese 2003). These pollutants require special attention in coastal areas due to their toxicity and persistence in the environment (Skeaff et al 2002). This concept is particularly important in those coastal environments, which include large industrial nuclei (such as Bahía Blanca estuary); consequently, a permanent input of pollutants occurs, which can produce a significant damage for the ecosystem .…”
mentioning
confidence: 99%
“…This can happen through larger scale resuspension events (e.g., currents, dredging, and other disturbances) or © 2019 The Authors wileyonlinelibrary.com/ETC µ FIGURE 3: Time series of dissolved copper data from the MELIMEX enclosure study (Gächter 1979). Data points are measured data from Gächter and Geiger (1979 Although some remobilization of copper was indicated in certain studies, Skeaff et al (2002) concluded that the net flux of metals was generally directed toward the sediment. Data from additional studies described in the Acid-volatile sulfide oxidation, Changes in redox conditions and the effect on bioavailability, and Resuspension events sections provide more insight into the potential remobilization of copper from sediments.…”
Section: Studies On Remobilization Of Copper From Sedimentsmentioning
confidence: 99%
“…Skeaff et al () proposed an approach to assessing metal "degradability" in the context of loss from the water column using metal "half‐times" (analogous to degradation half‐life) as a metric. This approach also considered the permanence of removal by looking at the extent of metal remobilization from sediment.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation